(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Many epidemiologic studies throughout globe have repeatedly shown negative affect of air contamination on humanoid fitnessiness, & it has estimated that more than 7 million public die each year as consequence of air contamination .. Furthermore to deprived air quality, re is growing evidence that interior air contamination is a significant danger to humanoid fitnessiness, particularly in lower-income nations where biomass fuels are still used as an energy source. When concentration of certain chemicals in atmosphere exceeds a specific level, air contamination occurs, which is detrimental to ecological system as well as normal circumstances of human life & growth. Scholars have undertaken a considerable amount of relevant study in face of increasingly severe environmental contamination issues, & air contamination forecasting has of vital significance in those studies. As preventive measure, air contamination forecasting is foundation aimed at implementing effective contamination management measures, & precised air contamination predicting has become a critical job. This review covers what is currently known about air contamination in low-income communities.